cos (

**v**- u ) = cos(**v**) * cos(u) + sin(**v**) * sin(u) since both u and**v**are in the II Quadrant, using sin(theta) = p/h , and...3 Answers · Science & Mathematics · 26/03/2011

...problem is not too hard. What you need to find is tan u and tan

**v**. You can do this given sin u and cos**v**. Sin is opposite...2 Answers · Science & Mathematics · 09/07/2008

Muller

**v**. Oregon, 208 U.S. 412 (1908), was a landmark decision... decided a mere three years after Lochner**v**. New York, 198 U.S. 45 (1905), in which a ...4 Answers · Education & Reference · 29/11/2007

600/(

**v**+30) + 600/(**v**-30) = 4.5 600[1/(**v**+30) + 1(**v**-30)] = 4.5 multiply with (**v**^2 - 900) 600[**v**-30 +**v**+ 30...2 - 2400v - 8100 = 0 9v^2 - 2430v + 30v - 8100 = 0 9v(**v**- 270) + 30(**v**- 270) = 0 (**v**-270)(9v + 30) = 0**v**= 270 or -10/34 Answers · Science & Mathematics · 12/12/2007

||

**v**|| = sqrt(x^2 + y^2). Square the x and y components. Add. Take the square root. Do the same with w to get ||w||. ||**v**|| - ||w|| means take the value of ||**v**| and the value of ||w|| and subtract. "...1 Answers · Science & Mathematics · 08/07/2013

for

**v**to be an eigen**v**ector with eigen**v**alue λ A**v**= λ**v**a) A**v**= λ**v**multiply by A A...multiply by A^-2 A^-2 A**v**= A^-2 λ**v**A^-1**v**= λ A^-2**v**= (λ A^-2)**v**for...1 Answers · Science & Mathematics · 31/01/2013

**v**-(4-**v**)=-2(2v-1)**v**-4+**v**=-4v+2 2v-4=-4v+2 2v+4v=2+4 6v=6**v**=1 answer checking 1-(4-1)=-2(2(1)-1) 1-3=-2(2-1) -2=-2 check12 Answers · Science & Mathematics · 16/02/2011

**v**/**v**% means the amounts of each liquid in the mix were ...how much of each water and methanol was in your original solution (the**v**/**v**% of each), and you know you added 47ml vs. 44, then you can uses...1 Answers · Science & Mathematics · 01/04/2010

Bowers

**v**. Hardwick, 478 U.S. 186 (1986), was a United... Court directly overruled Bowers in Lawrence**v**. Texas, 539 U.S. 558 (2003), and held that such ...2 Answers · Politics & Government · 01/11/2009

**v**^3+12v^2+36v Factor out the common factor:**v**(**v**^2+12v+36) Factor the remaining quadratic:**v**(**v**+ 6)^22 Answers · Science & Mathematics · 06/02/2011